DETEKSI JARI TANGAN BERBASIS KAMERA UNTUK PENGENDALIAN ALAT MUSIK ANGKLUNG - Mina Ismu Rahayu; Yus Jayusman; Azis Erdiyana (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2015)
Applications Finger Detection Based Camera For Angklung Instruments Control is educationalapplications that are expected to help preserve the culture, especially the angklung art, with the use oftechnology, in terms of appearance and also does not require a lot of people to play it is expected to simplifythe process learn the basics of the conductor of angklung.This application is built using the algorithm COG is how the agoritma this is by finding the midpoint of theobject hand by comparing the horizontal and vertical lines of an object, after the midpoint is found and thepoints are determined on a finger and create conditions in which the dots are connected and make handmovements where each movement has a value, then the output value is converted into sound. Prototypesoftware development methodology used by the system design using UML. Creating an application thatuses Visual Studio 10 Software and OpenCV libraries for application agoritma COG. Keyword: Angklungconductor applications, Finger Detection using OpenCV, Angklung, algorithm implementation COGKeyword: conductor applications, detection of fingers, Angklung